Control diet in a high-fat diet study in mice: Regular chow and purified low-fat diet have similar effects on phenotypic, metabolic, and behavioral outcomes. (2nd January 2019) - Almeida-Suhett, Camila P.; Scott, Jonathan M.; Graham, Alice; Chen, Yifan; Deuster, Patricia A.
Abstract : Background: Differences in the composition of control diets may confound outcomes in studies investigating dietary effects. Objective: We compared the effects of two control diets commonly used in mice studies, chow (SD) and a purified low-fat diet (LFD), in relation to a chronic high-fat diet (HFD). We hypothesized that SD and LFD will have similar effects on phenotypic, metabolic, and behavioral outcomes. Methods: Fifty-four 5-week-old male C57BL/6J mice were randomly assigned to one of the three dietary interventions (SD, LFD, or HFD) for 18 weeks. At week 16, mice were tested for behavioral changes. Glucose tolerance testing was conducted at week 17 and terminal blood collection at week 18. Results: SD and LFD mice exhibited no differences in cognitive performance on the Y-maze test and comparable anxiety-like behavior in the open-field and elevated zero maze tests. Significant declines in cognitive function and greater anxiety-like behavior were observed in the HFD group compared to both SD and LFD. Areas under the glucose tolerance curve were similar for SD and LFD, as were levels of high-density lipoprotein, triglycerides, cytokines, and adipocytokines. Only total cholesterol was significantly higher in LFD mice compared to SD mice. All measures were significantly higher in the HFD group. Discussion: Our data demonstrate that young mice develop similar phenotypic, metabolic, and behavioral profiles when fed SD vs. LFD. The two diets may thus be equally appropriate as controls for an HFD, although some studies may want to consider differences in effects on cholesterol levels.